Struktur Ilmu Menurut Islam: Pemikiran Ismail Raji Al-Faruqi - Masrur Salamuddin; Syamsul Rijal; Firdaus M. Yunus (Jurnal Seumubeuet, 2025)
The development of modern science has significantly advanced human civilization, yet it has also triggered an epistemological and spiritual crisis rooted in secularism, which separates revelation from reason. Ismail Raji al-Faruqi, a prominent contemporary Muslim thinker, identified this crisis as the loss of the tawhidic foundation within the structure of knowledge. This article aims to explore al-Faruqi’s conception of the Islamic structure of knowledge and its contribution to formulating a tawhid-based scientific paradigm. The study employs a qualitative-descriptive method using a library research approach, analyzing al-Faruqi’s primary works and secondary literature on modern Islamic epistemology. Data are examined through content analysis and a historical-philosophical approach to contextualize the emergence of the Islamization of knowledge and its underlying tawhidic principles. The findings reveal that al-Faruqi perceives Western modern science as suffering from a value crisis caused by the separation of revelation and reason, resulting in the exclusion of divine guidance from knowledge production. He proposes an alternative paradigm through the concept of Islamization of Knowledge, emphasizing tawhid as the ontological, epistemological, and axiological foundation of science. Within this unified structure, no dichotomy exists between religious and worldly sciences; both are integral to understanding divine will. The study concludes that al-Faruqi’s thought offers a significant contribution to the reconstruction of Islamic epistemology that integrates revelation, reason, and experience. The Islamic structure of knowledge formulated by al-Faruqi provides a conceptual basis for developing an ethical, just, and spiritually grounded Islamic civilization.